TechCare: Transformative Innovations in Addressing the Psychosocial Challenges of Cancer Care in Kerala, India - Mohammed Raqib; Prema Naittee George (Indian Journal of Medical and Paediatric Oncology)
As the global burden of cancer continues to escalate, the holistic care of patients demands innovative approaches that extend beyond medical interventions. This article delves into the transformative landscape of cancer care in Kerala, India, focusing on the intersection of technology and psycho-oncology. Examining the role of the state government, Kerala Startup Mission (KSUM), and individual startups and institutions, including Malabar Cancer Institute and Cochin Cancer Research Centre, we explore how technological innovations, telemedicine, and e-health solutions are actively shaping psycho-oncological support. Leveraging on case studies, we identify notable innovations, including artificial intelligence-based cancer screening, personalized treatment plans, and mental health support. The results signify a paradigm shift toward comprehensive, patient-centric cancer care, potentially influencing broader health care strategies. Despite acknowledging regional specificity and potential biases, the study underscores the transformative role of technological entrepreneurship in revolutionizing cancer care, paving avenues for future research for integrating psycho-oncological support in health care policies and startup initiatives. Overall, the article highlights the evolving landscape in Kerala as a beacon for holistic and patient-centric strategies that prioritize mental health alongside medical interventions.